A Systematic Review on Evaluation of WHO Core Prescribing Indicators Across Healthcare Facilities in Low Resource Asian Setting: A Case of Nepal - Rohit Agrawal B.Pharm; Rajeev Shrestha B.Pharm; Ramesh Sharma Poudel PhD; Shakti Shrestha PhD (Inquiry: The Journal of Health Care Organization, Provision, and Financing)
Inappropriate drug use is a significant global health issue, particularly in low-resource settings. This systematic review evaluates drug utilization across healthcare facilities in Nepal, a low-resource setting, using WHO core prescribing indicators to identify areas for improvement. A systematic review was conducted by searching literature in PubMed, Embase, CINAHL, INRUD bibliography, NepJOL, NepMed, and Google Scholar. Original studies assessing at least one WHO prescribing indicator in healthcare settings of Nepal were included. Eligible studies were analyzed descriptively and through proportional meta-analysis using a random-effects model. Eighty-eight studies were identified involving 2108 healthcare facilities and 60 191 patient encounters. The average of three drugs per encounter (95% CI: 2.5-3.2) was determined. Generic prescribing occurred only in 21.8% (95% CI: 15.6%-28.8%) prescriptions, showing a decline trend. Antibiotics were prescribed in 64.4% (95% CI: 57.7%-70.8%) encounters, with higher prevalence in secondary and tertiary care settings. Injectables were prescribed in 22.9% encounters (95% CI: 12.2-35.8). Drugs prescribed from WHO and Nepal essential medicine lists accounted for 53.0% (95% CI: 41.1-64.7) and 54.4% (95% CI: 47.7-60.9), respectively. The evaluation of drug utilization in Nepal suggested that the standards for WHO core prescribing indicators were not met, including overuse of antibiotics, underuse of essential medicines, and minimal generic prescribing. Targeted interventions, including prescriber education, policy reforms, enhanced monitoring, and regular prescription audits, are essential to promote rational prescribing and improve drug-related outcomes, including an opportunity to reduce antimicrobial resistance.